2010
DOI: 10.1063/1.3477952
|View full text |Cite
|
Sign up to set email alerts
|

Large internal dipole moment in InGaN/GaN quantum dots

Abstract: Direct observation of large permanent dipole moments of excitonic complexes in InGaN/GaN quantum dots is reported. Characteristic traces of spectral diffusion, observed in cathodoluminescence of InGaN/GaN quantum dots, allow deducing the magnitude of the intrinsic dipole moment. Our experimental results are in good agreement with realistic calculations of quantum dot transition energies for position-dependent external electric fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…The disadvantage of the internal electric fields, however, is the spatial separation of the electron and hole wavefunctions that reduces the radiative recombination efficiency due to the quantum confined Stark effect (QCSE), and which leads to long exciton lifetimes increasing the time-jitter on the emission from a single photon source and reducing the available repetition rate. These in-built electric fields may also be responsible for spectral diffusion (the variation of the QD emission wavelength on a timescale of a few seconds), which makes maintaining resonance between a QD and an optical cavity difficult 5 . Growth of InGaN QDs along non-and semi-polar orientations is thus of interest since the internal electric fields can be greatly reduced or eliminated 6,7 .…”
mentioning
confidence: 99%
“…The disadvantage of the internal electric fields, however, is the spatial separation of the electron and hole wavefunctions that reduces the radiative recombination efficiency due to the quantum confined Stark effect (QCSE), and which leads to long exciton lifetimes increasing the time-jitter on the emission from a single photon source and reducing the available repetition rate. These in-built electric fields may also be responsible for spectral diffusion (the variation of the QD emission wavelength on a timescale of a few seconds), which makes maintaining resonance between a QD and an optical cavity difficult 5 . Growth of InGaN QDs along non-and semi-polar orientations is thus of interest since the internal electric fields can be greatly reduced or eliminated 6,7 .…”
mentioning
confidence: 99%
“…The presence of the internal electric field may also be responsible for the variation in the emission wavelength and linewidth over time (spectral diffusion). 6 Theoretical work has suggested that growth in the non-polar orientations may eliminate the in-plane electric field. 7 Previous work by Zhu et al 8 has demonstrated the growth of non-polar a-plane InGaN QDs by the modified droplet epitaxy (MDE) method with exciton lifetimes an order of magnitude smaller than comparable polar QDs, 9 and which exhibit improved temperature stability 10 and Rabi oscillations.…”
mentioning
confidence: 99%
“…It establishes that the equation governing the dynamics of the excited-state population, n(t) = |c(t)| 2 , for an initially excited QE is The spheres radius is 120 nm (so that 1 δ 10 nm), and µ E = 1.5 e · nm (InGaN/GaN quantum dots at 3 eV [25]). The emitter is at resonance with the lowest (dipolar) SP (b) and with the pseudomode (c) maxima in Figure 2(a), respectively.…”
mentioning
confidence: 99%